ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA RUMAH SAKIT MUHAMMADIYAH KOTA METRO - Nita Ismaya; Suyanto Suyanto; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2021)
This study aims to find out the Accounting Information System for Cash Receipts and Expenditures at Muhammadiyah Hospital in Metro City. The data is obtained from interviews, observations, and documentations. Research data analysis was conducted using qualitative descriptive data analysis. The results show that the procedure of receipt and expenditure of cash has been implemented properly where the evidence of receipt and expenditure of cash are reported and stored by the authorities. In addition, records are begun from journals, ledgers to financial statements.